Irregular Migrants in Belgium and the Netherlands : Aspirations and Incorporation - Meeteren, Masja van (Book collections on Project MUSE., 2014)
Proposing an empirically grounded theoretical critique of the dominant research practice that focuses on survival strategies, van Meeteren takes irregular migrants aspirations as a starting point of analysis. Drawing on intensive participant observation, as well as more than 200 in-depth interviews with irregular migrants and representatives of organisations working with them, she develops much-needed contextualised insights and sheds new light on earlier debates on this top-of the-agenda subject area.